2021
DOI: 10.3389/fonc.2021.772263
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathways and Targets in Chondrosarcoma

Abstract: Chondrosarcomas are the second most common primary bone malignancy. Chondrosarcomas are characterized by the production of cartilaginous matrix and are generally resistant to radiation and chemotherapy and the outcomes are overall poor. Hence, there is strong interest in determining mechanisms of cancer aggressiveness and therapeutic resistance in chondrosarcomas. There are metabolic alterations in chondrosarcoma that are linked to the epigenetic state and tumor microenvironment that drive treatment resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Currently torisel and liposomal doxorubicin are tested in patients with advanced soft tissue and bone sarcomas in Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins University in a NCT00949325 trial. In another mTOR trial, sapanisertib was tested only in xenografts and cell lines [180].…”
Section: Targeted Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently torisel and liposomal doxorubicin are tested in patients with advanced soft tissue and bone sarcomas in Sidney Kimmel Comprehensive Cancer Center at Johns Hopkins University in a NCT00949325 trial. In another mTOR trial, sapanisertib was tested only in xenografts and cell lines [180].…”
Section: Targeted Treatmentmentioning
confidence: 99%
“…In addition to the signaling pathways mentioned, chondrosarcoma also exhibits strong activation of the Hedgehog pathway and GDC-0449 (Hedgehog inhibitor) is of interest in chondrosarcoma [180]. The French Sarcoma Group, in phase II of a collaborative study of antagonists of the Hedgehog signal pathway vismodegib (GDC-0449) in patients with advanced CS (11% DDCS), administered 150 mg/day GDC-0449 in a 28-day cycle.…”
Section: Targeted Treatmentmentioning
confidence: 99%
“…7 Chondrosarcomas are a group of different types of malignancies with distinct histopathological features characterized by the production of cartilage matrix. 8 Most chondrosarcomas are slow growing, rarely metastasize, and adequate surgery can lead to a good prognosis. 9 However, because of the poor sensitivity of high-grade chondrosarcoma to radiotherapy and chemotherapy, adequate surgical resection may be the better option.…”
Section: Introductionmentioning
confidence: 99%
“…7 Chondrosarcomas are a group of different types of malignancies with distinct histopathological features characterized by the production of cartilage matrix. 8…”
Section: Introductionmentioning
confidence: 99%
“…However, the structure of Homo sapiens IDH2 and other point mutants associated with cancers remains unclear. Numerous studies have shown that IDH1/IDH2 mutations frequently occur in low-grade gliomas 7 , secondary glioblastoma 8 , chondrosarcoma 9 , acute myeloid leukemia (AML) 10 , and intrahepatic cholangiocarcinoma 11 . Point mutations are mainly found in the arginine residues within the isocitrate binding sites of IDH active sites , including IDH1/R132, IDH2/R140, and IDH2/R172.…”
Section: Introductionmentioning
confidence: 99%